Understanding the Origin of Formation and Active Sites for Thiomolybdate [Mo3S13](2-) Clusters as Hydrogen Evolution Catalyst through the Selective Control of Sulfur Atoms - Lee, Cheol-Ho; Lee, Sungho; Lee, Youn-Ki; Jung, Yong Chae; Ko, Yong-Il; Lee, Doh C.; Joh, Han-Ik (AMER CHEMICAL SOC, 2018)
[Mo3S13](2-) clusters have become known as one of the most efficient catalysts for the hydrogen evolution reaction (HER) because most of the sulfur (S) atoms in the cluster are exposed, resulting in many active sites. However, the origin of the cluster formation and active S sites in the cluster is unknown, hindering the development of efficient catalysts. Herein, the mechanism of the transition from amorphous MoS3 to [Mo3S13](2-) clusters is systematically investigated. In addition, the active S sites have been identified by the selective removal of S atoms via low-temperature heat treatment. In summary, we believe that the clusters grow from amorphous MoS3 with apical S atoms, and bridging S atoms are the active HER sites in the [Mo3S13](2-) clusters. The clusters deposited on carbon nanotubes exhibited good electrochemical HER activity with a low onset potential of 96 mV, a Tafel slope of 40 mV/decade, and stability for 1000 cycles.
Keywords: AMORPHOUS MOLYBDENUM SULFIDE; EDGE SITES; MOS2; OXIDATION; ELECTROCATALYSIS; DECOMPOSITION; GRAPHENE; KINETICS; OXYGEN; H-2